Pengaruh Ekstrak Rimpang Kencur (Kaempferia galanga L.) terhadap Tingkat Kesembuhan Benih Ikan Lele Dumbo (Clarias sp.) yang Terinfeksi Saprolegnia sp. [Effect of Rhizome Extract (Kaempferia kalanga L.) for the Cure Rate of Catfish (Clarias sp.) Infected by Saprolegnia sp. ] - Hari Suprapto; Nadia Fierias Fathma Riza; Rahayu Kusdarwati (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Saprolegnia sp. is a fungus that causes the disease Saprolegniasis on eggs and fresh water fish such as catfish (Clarias sp.). Treatment of Saprolegniasis have done using chemical drugs such as malachite green, formalin, sodium chloride and asetic acid. However, the use of chemical drugs is bad for the environment and biota. The purpose of this study is to determined the antifungal activity from rhizome extract (Kaempferia galanga L.) for the cure rate of catfish fry (Clarias sp) infected by Saprolegnia sp. The research was conducted on June 2013 at Fisheries and Marine Faculty of Airlangga University. The method used in this study is experimental method using Kruskall Wallis followed by Two Sample Independent test design with 5 treatments and four repetitions. Results showed that the extract of Kaempferia galanga L. has antifungal activity to recovery infected catfish fry. The optimal concentration from this research is 64%. The existence of antifungal activity of Kaempferia galanga L. extracts to Saprolegnia sp. showed that Kaempferia galanga L. extract consists some compounds as fungistatic and fungicidal such as flavonoid, saponin, phenolic and essential oil compounds.